Bioaccumulation and trophic transfer of PAHs in tropical marine food webs from coral reef ecosystems, the South China Sea: Compositional pattern, driving factors, ecological aspects, and risk assessment. (December 2022) - Han, Minwei; Li, Haolan; Kang, Yaru; Liu, Huanxin; Huang, Xueyong; Zhang, Ruijie; Yu, Kefu
Abstract: Multiple environmental pressures caused by global warming and human activities have aroused widespread concern about PAHs pollution in tropical marine coral reef regions (CRRs). However, the trophodynamics of PAHs in the food webs of the CRRs and the related influence factors have not been reported. This study investigated the occurrence, trophic amplification, and transmission of PAHs in various organisms selecting between at least representative species for each level in CRRs of the South China Sea (SCS); revealed their driving mechanisms; and explored the trophodynamics of PAHs in the food web of the coral reef ecosystem. Results showed that more PAHs can be accumulated in the mantle tissue of Tridacnidae, and the proportion of mantle tissue of Tridacnidae increases with the increase of latitude (y = 0.01x + 0.17, R 2  = 0.49, p  < 0.05). Latitude drives the differential occurrence level and bioaccumulation of PAHs in tropical marine organisms, and also affects the trophodynamics of PAHs in aquatic ecosystem food webs. PAHs undergo trophic amplification in the food webs of tropical marine ecosystems represented by coral reefs, thus further aggravating the negative environmental impact on coral reef ecosystems. The cancer risk caused by accidental ingestion of PAHs by humans through consumption of seafood in CRRs is very low, but we should be alert to the biomagnification effect of PAHs. Graphical abstract: Image 1 Highlights: Reported PAHs' occurrence in the coral reef food web for the first time. Latitude affected PAHs' occurrence and bioaccumulation in the organisms. Latitude drove the PAHs' trophodynamics in aquatic ecosystem food webs. PAHs underwent trophic amplification in the food webs of coral reef ecosystems.